2016
DOI: 10.1074/jbc.m115.696088
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Investigation of Structure/Function Requirements for the Apolipoprotein A-I/Lecithin Cholesterol Acyltransferase Interaction Loop of High-density Lipoprotein

Abstract: The interaction of lecithin-cholesterol acyltransferase (LCAT) with apolipoprotein A-I (apoA-I) plays a critical role in highdensity lipoprotein (HDL) maturation. We previously identified a highly solvent-exposed apoA-I loop domain (Leu 159 Apolipoprotein A-I (apoA-I), the major protein component of high-density lipoprotein (HDL), transports lipids and also serves as a protein scaffold for numerous HDL-associated protein interactions. The HDL particle is responsible for facilitating reverse cholesterol transpo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
13
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 47 publications
4
13
0
Order By: Relevance
“…These findings agree with previous experimental reports showing that apoA-I increases the binding of LCAT to lipids compared to apolipoprotein-free small unilamellar vesicles (Jin et al, 1999;Jonas, 2000). Earlier it has been shown that the apoA-I mutation Y166F decreases the surface binding and activity of LCAT which is in agreement with our experimental results (Gu et al, 2016;Wu et al, 2007). In general, many studies have pointed out that the charged and polar amino acids located in the central parts of apoA-I are important in LCAT activity (Sorci-Thomas et al, 2009;Sorci-Thomas and Thomas, 2002).…”
Section: Discussionsupporting
confidence: 94%
“…These findings agree with previous experimental reports showing that apoA-I increases the binding of LCAT to lipids compared to apolipoprotein-free small unilamellar vesicles (Jin et al, 1999;Jonas, 2000). Earlier it has been shown that the apoA-I mutation Y166F decreases the surface binding and activity of LCAT which is in agreement with our experimental results (Gu et al, 2016;Wu et al, 2007). In general, many studies have pointed out that the charged and polar amino acids located in the central parts of apoA-I are important in LCAT activity (Sorci-Thomas et al, 2009;Sorci-Thomas and Thomas, 2002).…”
Section: Discussionsupporting
confidence: 94%
“…S5, and Table 2). The K d of 0.72 M obtained for WT LCAT is consistent with previous studies (14,38,39). ⌬N⌬C was the most defective in this analysis, decreasing the K d value by an order of magnitude, consistent with a role for the N terminus in HDL binding.…”
Section: Lid Variants Exhibit Defects In Hdl Bindingsupporting
confidence: 91%
“…We measured the binding of varying concentrations of LCAT to immobilized rHDL substrates to determine equilibrium binding constants. Figure 6 shows that LCAT bound to WT rHDL with a K D of 1.9-2.1 M, consistent with previous reports (46). K133C rHDL exhibited a similar K D of 0.7 M.…”
Section: Effect Of Apoa1 Helical Registry On Lcat Binding Affinitysupporting
confidence: 89%